Greener cities, cleaner homes: Evaluating the effect of China's low-carbon city pilot policy on urban household energy consumption structure - Yunchang Wang; Yanjun Ren; Jieyu Yang; Mi Zhou; Qiran Zhao (Energy Policy, 2026)

The Roles of DMT1 in Inflammatory and Degenerative Diseases - Haigang Liu; Mi Li; Yi Deng; Yanjun Hou; Liangcai Hou; Xiong Zhang; Zehang Zheng; Fengjing Guo; Kai Sun (Molecular Neurobiology, 2025)

Supply and demand of ecosystem services and their interaction with urbanization: The case of Chengdu-Chongqing urban agglomeration - Yuqi Xie; Wencai Dai; Shujiang Xiang; Hua Deng; Zifang Wang; Yanjun Li; Zhongshu Wang; Mi Zhou; Ming Gao (Urban Climate, 2024)

Highly sensitively detection of amine vapors released during shrimp spoilage by fluorescent molecules locked in covalent organic frameworks - Jingru Mi; Yongxian Guo; Yanjun Gong; Shuya Liu; Mei Zhao; Qiongzheng Hu; Li Yu (Food Chemistry, 2023)

microRNA-499a promotes the progression and chemoresistance of cervical cancer cells by targeting SOX6 - Yibing Chen; Yucen Song; Yanjun Mi; Huan Jin; Jun Cao; Haolong Li; Liping Han; Ting Huang; Xiaofei Zhang; Shumin Ren; Qian Ma; Zhengzhi Zou (Apoptosis, 2020)

Growing‐season temperature and precipitation are independent drivers of global variation in xylem hydraulic conductivity - Pengcheng He; Sean M. Gleason; Ian J. Wright; Ensheng Weng; Hui Liu; Shidan Zhu; Mingzhen Lu; Qi Luo; Ronghua Li; Guilin Wu; Enrong Yan; Yanjun Song; et al. (Global Change Biology, 2020)
Stem xylem‐specific hydraulic conductivity ( K S ) represents the potential for plant water transport normalized by xylem cross section, length, and driving force. Variation in K S has implications for plant transpiration and photosynthesis, growth and survival, and also the geographic distribution of species. Clarifying the global‐scale patterns of K S and its major drivers is needed to achieve a better understanding of how plants adapt to different environmental conditions, particularly under climate change scenarios. Here, we compiled a xylem hydraulics dataset with 1,186 species‐at‐site combinations (975 woody species representing 146 families, from 199 sites worldwide), and investigated how K S varied with climatic variables, plant functional types, and biomes. Growing‐season temperature and growing‐season precipitation drove global variation in K S independently. Both the mean and the variation in K S were highest in the warm and wet tropical regions, and lower in cold and dry regions, such as tundra and desert biomes. Our results suggest that future warming and redistribution of seasonal precipitation may have a significant impact on species functional diversity, and is likely to be particularly important in regions becoming warmer or drier, such as high latitudes. This highlights an important role for K S in predicting shifts in community composition in the face of climate change.

An integrated UAV-borne lidar system for 3D habitat mapping in three forest ecosystems across China - Qinghua Guo; Yanjun Su; Tianyu Hu; Xiaoqian Zhao; Fangfang Wu; Yumei Li; Jin Liu; Linhai Chen; Guangcai Xu; Guanghui Lin; Yi Zheng; Yiqiong Lin; et al. (International Journal of Remote Sensing, 2017)

Intraspecific and phylogenetic density-dependent seedling recruitment in a subtropical evergreen forest - Yanjun Du; Simon A. Queenborough; Lei Chen; Yunquan Wang; Xiangcheng Mi; Keping Ma; Liza S. Comita (Oecologia, 2017)